Phase diagrams of three-lane asymmetrically coupled exclusion process with Langmuir kinetics. (26th November 2015) - Verma, Atul Kumar; Gupta, Arvind Kumar; Dhiman, Isha
Abstract: This letter studies a fully asymmetrically coupled three-lane totally asymmetric simple exclusion process with Langmuir kinetics under open boundary conditions. Phase diagrams and density profiles for different kinetic rates are obtained using a mean-field analysis along with a singular perturbation technique and are found to be in good agreement with Monte Carlo simulation results. Some mixed phases are observed in the middle lane resulting into bulk-induced phase transitions. We have found that a number of steady-state phases firstly increases then decreases with respect to an increase in lane changing rate. Critical values of the lane changing rate are identified at which the appearance or disappearance of certain phases is observed. We have identified the jumping effect in the position of shock in the middle lane with respect to an increase in the lane changing rate.